Fall Migration of Ringed Seals (Phoca hispida) through the Beaufort and Chukchi Seas, 2001–02 - Harwood, Lois A.; Smith, Thomas G.; Auld, James C. (ARCTIC, 2012)
In a study examining the range, distribution, and habitat use of the ringed seal, Phoca hispida, in Canada’s Western Arctic, eight ringed seals were live-captured, instrumented with satellite-linked (SLTDR-16) transmitters, and released at Cape Parry, Northwest Territories, Canada, on 17 – 19 September 2001 and 7 – 8 September 2002. Locations accepted by the filtering process were received from seven of the eight tagged seals (5 subadults, 1 adult female, 1 pup) over periods ranging from 35 to 207 days (mean 99 d, SD 66). Mean rates of travel were 0.91 m/s (SE 0.011, n = 7) in the Canadian Beaufort Sea, 0.92 m/s (SE 0.014, n = 7) offshore of Alaska’s North Slope, and 0.79 m/s (SE 0.008, n = 5) in the Chukchi Sea. On average, the seals took 32 days (range 19 – 56 d) to migrate between Cape Parry and Point Barrow, almost always remaining within 100 km of shore and over the continental shelf or slope, and covering an average migration distance of 2138 km. Dive depths for all groupings were mainly in the 4 – 80 m range (adult female: 63 – 73%; subadults: 54 – 73%; pup: 64 – 82%), with only the adult female diving deeper than 80 m on occasion, mainly in the Canadian Beaufort Sea (15.1% of her dives). The subadults and pup dove mainly for more than 1 to 5 min (60% and 55%, respectively), while a large proportion of the adult female’s dives were longer (34% for > 1 to 5 min; 31% for > 5 to 8 min; 5.4% for > 8 min). The tracks of the westward migrating seals revealed a routing through three political jurisdictions (including oil and gas industry lease areas in all three) over a period of about two months. This pattern highlights the importance of cooperation between the United States, Canada, and Russia in managing this species. Du 17 au 19 septembre 2001 et les 7 et 8 septembre 2002, dans le cadre d’une étude portant sur le parcours, la répartition et l’utilisation de l’habitat du phoque annelé, Phoca hispida, dans l’ouest de l’Arctique canadien, huit phoques annelés ont été capturés en vie, dotés de ...